The Contemporary Salience of Deprivation Theory: Prison Personnel Perceptions of Inmates and the Pains of Solitary Confinement - Aranda-Hughes, Vivian (Crime & delinquency, 2021)
In recent decades, long-term solitary confinement has become a mainstay of prison systems. Critiques and research of this confinement typically have focused on its potential harms. Few studies have examined the range of harms to those placed in it; fewer still have examined solitary confinement’s potential benefits or sought insight from those who work with them. Guided by Sykes’ deprivation theory, we draw on focus groups and interviews with 144 correctional personnel to examine their perceptions of incarcerated individuals’ experiences with, and responses to, deprivations of solitary confinement. We show that staff view the pains of imprisonment as potentially increasing or decreasing in solitary confinement and that they view incarcerated persons as adapting to such confinement in different ways.